Weather Risk Management Pilot Program : Tanzania - World Bank (Washington, DC, 2013)
A feasibility study to select the crop(s) and the area(s) to be covered in this pilot phase was completed by TechnoServe in August of 2006. The study identified maize as the most appropriate crop to pilot because it was identified as the most important food crop in Tanzania because it is grown mostly by smallholder farmers; it was highly susceptible to drought; and ample agronomic information was available on maize cultivation and the water requirements of the maize plant. Given the rapid timeline for implementation international experience already existed which could guide the design of the contract. Although coffee was also recommended for inclusion in a weather insurance pilot project as an important export crop, given the tight time line for the implementation of the pilot, it would have been very difficult to gather the necessary information for the development of an index that clearly demonstrated the correlation between rainfall and coffee production. The development of a coffee index would have required significant time spent on research and development which was not available, thus limiting the ability ofthe project team to include it in the pilot for the 2006/2007 growing season.